ACADSB regulates ferroptosis and affects the migration, invasion, and proliferation of colorectal cancer cells. (22nd August 2020) - Lu, Di; Yang, Zhiyu; Xia, Qiaoyun; Gao, Shanjun; Sun, Suofeng; Luo, Xiaoying; Li, Zhen; Zhang, XiuLei; Li, Xiuling
Abstract: Colorectal cancer (CRC) is one of the most pressing health issues in today's society. As such, it is imperative that the scientific community devise effective methods to inhibit the proliferation and metastasis of CRC cells. Ferroptosis is a recently discovered regulatory cell death mode mainly manifested by dysregulation of cellular iron metabolism and mitochondrial lipid peroxidation. ACADSB is a member of the acyl‐CoA dehydrogenase. This study finds that ACADSB is lowly expressed in CRC tissues. Its expression is negatively correlated with N‐ and M‐stage CRC but positively correlated with the overall survival rate of CRC patients. In addition, it finds that ACADSB is found in the mitochondria of cells. Overexpression of ACADSB inhibits CRC cell migration, invasion, and proliferation, while ACADSB knockdown has the opposite effect. More importantly, the study finds that ACADSB negatively regulates expression of glutathione reductase and glutathione peroxidase 4, the two main enzymes responsible for clearing glutathione (GSH) in CRC cells. ACADSB overexpression enhances the concentration of malondialdehyde, Fe +, superoxide dismutase, and lipid peroxidation in CRC cells, but reduces the concentration of GSH. This is significant, as all of these are important indicators of ferroptosis. Evaluating the data as a whole, this paper speculates that ACADSB affects CRC cell migration, invasion, and proliferation by regulating CRC cell ferroptosis.